2015
DOI: 10.15621/ijphy/2015/v2i5/78237
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dynamic Balance Training on Agility in Male Basketball Players

Abstract: Background: Athletes focus their training on two major goals, i.e., avoidance of the injury and increasing the performance. Balance training has been widely used in competitive sports to improve the balance and thus reduce the risk of injury, for example, ligamentous sprains, which are very common in Basketball. On the other hand, various drills are being used to improve the performance parameters such as agility. Our effort is to find out an exercise program which focuses on balance training and see whether i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…In the studies which examine the effects of balance trainings on balance, agility and speed; Saraswat et al, (2015) [18], found that 4 weeks of balance training significantly improved agility (p<0.05). In their study on the effects of 6-week dynamic balance studies on agility and vertical jump in football players, Güler and Eniseler (2017) [19], found that 6-week balance exercises significantly improve agility and explosive strength (p=0.005).…”
Section: Discussionmentioning
confidence: 99%
“…In the studies which examine the effects of balance trainings on balance, agility and speed; Saraswat et al, (2015) [18], found that 4 weeks of balance training significantly improved agility (p<0.05). In their study on the effects of 6-week dynamic balance studies on agility and vertical jump in football players, Güler and Eniseler (2017) [19], found that 6-week balance exercises significantly improve agility and explosive strength (p=0.005).…”
Section: Discussionmentioning
confidence: 99%
“…Twenty one studies applied a training intervention in addition to regular training and 7 studies used a warm-up intervention in place of the usual warm-up routine [14] [18] [31] [32] [36] [37] [38]. Stated compliance in the 10 IPPs ranged from 24–100% [50] [26] [27] [48] [17] [18] [10] [14] [33] [21] whereas 18 were undefined [23] [24] [25] [19] [28] [29] [30] [47] [34] [35] [39] [40] [41] [42] [51] [49] [44] [46].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 9 studies comprising of sports specific IPPs, 1 assessed dynamic balance [39], 1 static balance (2 overall measures) [45], 3 power (7 overall measures) [21] [40] [25], 3 strength (8 overall measures) [21] [44] [25], 4 speed/agility (9 overall measures) [40] [42] [43] [46] and 1 endurance [40] as a function of performance. The IPPs ranged from 1–20 different exercises lasting between 15-60min.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed examination of bias clearly shows variation in study quality, to the extent that the internal validity of some particular findings is questionable [35]. Despite the considerable differences among the studies, it is astonishing that in all of them the balance training interventions led to significant increases in agility and physical performance capacity [36][37][38][39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%